Sodium ion halide solid electrolyte composite membrane material and preparation method and application thereof

By using composite materials of sodium ion halides, specific binders, sodium salts and plasticizers, the complex problem of sodium ion halide solid-state battery assembly process is solved, and the effect of high room temperature ionic conductivity and simplified assembly process is achieved.

CN119447438APending Publication Date: 2025-02-14GUANGDONG POWER GRID CO LTD +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411665053.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The assembly process of sodium ion halide solid-state batteries is complex and difficult to apply to soft-pack batteries, which hinders its large-scale application in the energy storage industry.

Method used

Composite film materials are prepared by grinding and pressure application methods such as sodium ion halides, specific binders, sodium salts and plasticizers, and the assembly process of solid-state batteries is simplified.

Benefits of technology

The high room temperature ionic conductivity and good self-supporting performance of sodium ion halide solid electrolyte composite film material are achieved, greatly simplifying the assembly process of solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005144391260000131
    Figure BDA0005144391260000131
  • Figure BDA0005144391260000132
    Figure BDA0005144391260000132
  • Figure BDA0005144391260000141
    Figure BDA0005144391260000141
Patent Text Reader

Abstract

The invention relates to a sodion halide solid electrolyte composite membrane material as well as a preparation method and application thereof, and belongs to the technical field of solid electrolyte materials. The sodion halide solid electrolyte composite membrane material comprises sodion halide, a binder, sodium salt and a plasticizer, wherein the sodion halide is NaaMObXc, (a is greater than 0, b is greater than 0, and c is greater than 0), M is selected from transition metal elements, rare earth metal elements and the like, and X is halogen elements; based on the mass percentage of the sodium ion halide, the content of the binder is 0.5-2%, the content of the sodium salt is 5-12%, and the mass of the plasticizer is 0.1-0.3% of the mass of the sodium salt. The composite membrane material disclosed by the invention has high room-temperature ionic conductivity, is low in cost and simple to prepare, greatly simplifies the assembly process of a solid-state battery, and has very high application value in the field of secondary batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolyte materials, and in particular to a sodium ion halide solid electrolyte composite membrane material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries have the advantages of high energy density and long cycle life. Traditional sodium-ion batteries face severe safety issues due to the use of organic liquid electrolytes with poor thermal stability and low ignition point. If used improperly, they can easily cause fires or explosions. In order to completely solve the safety problem, it is a beneficial choice to use solid electrolytes with good thermal stability to replace organic liquid electrolytes. Solid electrolytes also have good compatibility with high-voltage cathodes, can reduce the dead mass of battery packs, and enable battery packs to achieve higher energy density.

[0003] According to the different chemical compositions, solid electrolytes can be roughly divided into three categories: inorganic electrolytes, polymer electrolytes and organic-inorganic composite electrolytes. Inorganic electrolytes have ionic conductivity close to that of liquid electrolytes, and show a wider electrochemical stability window and operating temperature window. According to the anion composition, inorganic electrolytes can be further divided into oxides, sulfides and halides. Among them, halide electrolytes are considered to be the best candidate materials for all-solid-state battery technology due to their inherent chemical properties.

[0004] Initially, Kendall et al. reported the ionic conductivity of LiX (X = Cl, F, Br, I), but its low ionic conductivity did not attract widespread attention (J. Am. Chem. Soc., 1923, 45, 963-996). In 2018, Asano and colleagues synthesized the trigonal Li 3 YC 6 and monoclinic Li 3 Yb 6 , showing excellent room temperature ionic conductivity (AdvMater.2018,30,1803075), which is several orders of magnitude higher than previously reported halide solid electrolytes. In addition, the strategy of doping heterogeneous anions in the halide matrix can enhance the conductivity of ions, which is comparable to liquid electrolytes at room temperature (Angew.Chem.,Int.Ed.,2023,62,e202217581;Nat.Mater.,2015,14,1026-1031). Compared with lithium, sodium has a more abundant source and lower cost. Therefore, the research on sodium solid electrolytes is expected to become the direction of future development. However, the current sodium ion halide solid electrolytes still have the problem of complex battery assembly operation, which makes it difficult to apply to soft-pack batteries, hindering its large-scale application in the energy storage industry.

[0005] Therefore, developing a suitable sodium ion halide modification method and simplifying the assembly process of sodium ion halide solid-state batteries have high application prospects and can promote the development of sodium ion halides in the field of solid-state batteries. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a sodium ion halide solid electrolyte composite membrane material and its preparation method and application. The sodium ion halide solid electrolyte composite membrane material provided by the present invention has high room temperature ionic conductivity and greatly simplifies the assembly process of sodium ion halide solid-state batteries, and has broad application prospects.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] In a first aspect, the present invention provides a sodium ion halide solid electrolyte composite membrane material, comprising the following components: sodium ion halide, a binder, a sodium salt, and a plasticizer;

[0009] The sodium ion halide is Na a MO b X c , a>0, b>0, c>0, M is at least one of Cr, V, Fe, Co, Ni, Ti, Sc, Lu, Y, Al, Ga, In, Yb, Tm, Er, Ho, Dy, Tb, Gd, Eu, Sm, Pm, Nd, Pr, Ce, La, Ti, Zr, Hf, Sn, Ge, Si, Nb, and Ta, and X is at least one of F, Cl, Br, and I;

[0010] The binder comprises at least one of polytetrafluoroethylene, polytetrafluoroethylene hexafluoroisopropylene block copolymer, polyvinylidene fluoride, polyethylene oxide, polypropylene oxide, polyethylene oxide propylene oxide block copolymer, chloroprene rubber, nitrile rubber, ethylene propylene diene monomer rubber, and natural rubber;

[0011] The sodium salt includes at least one of sodium bis(trifluoromethanesulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorophosphate, and sodium difluorooxalate borate;

[0012] Calculated by mass percentage of the sodium ion halide, the content of the binder is 0.5-2%, the content of the sodium salt is 5-12%; the mass of the plasticizer is 1-3% of the mass of the sodium salt.

[0013] In view of the problem that sodium ion halide solid electrolyte has complicated battery assembly operation, the present invention provides a sodium ion halide solid electrolyte composite membrane material, which is improved by compounding a specific sodium ion halide with a specific binder and sodium salt, and a plasticizer; the present invention finds through research that after compounding with a binder, a sodium salt, and a plasticizer, the sodium ion halide solid electrolyte maintains a high room temperature ionic conductivity (>10 -4 S / cm), while greatly simplifying the assembly process of solid-state batteries.

[0014] The present invention defines a specific sodium ion halide, wherein the relatively large ionic radius of the anion is conducive to the dissociation of the ion, and can form a wider ion transmission channel, which is conducive to ion migration, thereby ensuring the high ionic conductivity of the halide solid electrolyte. Compared with oxides and sulfides, the halide anion has a lower binding strength with polyanions, a softer lattice structure, and a higher anion polarizability, which gives the halide solid electrolyte good mechanical deformation ability and is conducive to the assembly of all-solid-state batteries.

[0015] The binder is preferably selected from at least one of polytetrafluoroethylene (PTFE), polytetrafluoroethylene hexafluoroisopropylene block copolymer (PTFE-HFP), polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polypropylene oxide (PPO), polyethylene oxide propylene oxide block copolymer (PEO-co-PO), chloroprene rubber (CR), nitrile rubber (NBR), ethylene propylene diene rubber (EPDM), and natural rubber (NR); the sodium salt is preferably selected from sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium bis(fluorosulfonyl)imide (NaFSI), sodium difluorophosphate (NaPO 2 F 2 ), sodium difluorooxalate borate (NaDFOB).

[0016] The present invention can give the composite membrane a better self-supporting ability as a whole while maintaining the high room temperature ionic conductivity of the sodium ion halide by selecting a binder of appropriate type and amount. Excessive binder will reduce the ionic conductivity of the sodium ion halide matrix; too little binder will cause the membrane to be fragile and unable to self-support. A specific type of binder has little effect on the room temperature ionic conductivity, but a binder without ion transmission ability significantly reduces the room temperature ionic conductivity.

[0017] At the same time, the type and amount of sodium salt and the amount of plasticizer also have a great influence on the room temperature ionic conductivity of the sodium ion halide solid electrolyte composite membrane material of the present invention: an appropriate amount of sodium salt can promote ion transport in the composite membrane, while an excessive amount of sodium salt will cause self-crystallization and agglomeration, resulting in obstruction of ion transport; an appropriate amount of plasticizer can inhibit the crystallization of sodium salt and improve the sodium ion transport capacity of the composite membrane, but an excessive amount of plasticizer without ion transport capacity will inhibit the transport process of sodium ions.

[0018] Preferably, the sodium ion halide comprises Na 1.8 NbO 0.9 Cl 5 、NaTaOCl 5 、Na 1.6 HkDJ 0.8 Cl 4 、Na 1.6 S 0.8 Cl 3 、Na 1.2 La 0.5 Ta 0.5 O 0.6 Cl 4 、Na 2.2 YO 0.7 Cl 3.8 It should be noted that the selection scheme of the sodium ion halide of the present invention is not limited to the above-mentioned specific ones. Those skilled in the art can adjust or replace the doping elements and doping ratios within the limited range of the sodium ion halide solid electrolyte composite membrane material of the present invention according to actual needs.

[0019] Preferably, the sodium ion halide solid electrolyte composite membrane material also includes an organic solvent.

[0020] Further preferably, the organic solvent includes at least one of N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), chloroform, ethylene dichloride, benzene, toluene, ethyl acetate, butyl acetate, methyl ethyl ketone, cyclohexane, turpentine, and naphtha.

[0021] As a preferred embodiment, when the binder is polyethylene oxide propylene oxide block copolymer (PEO-co-PO), the organic solvent is selected from at least one of chloroform, ethylene dichloride, benzene, and toluene; when the binder is ethylene propylene diene monomer rubber (EPDM) or natural rubber (NR), the organic solvent is selected from at least one of cyclohexane, turpentine, and naphtha. The role of introducing the organic solvent in the present invention is to promote the dispersion and mixing of the components and to facilitate the formation of a relatively uniform film; however, in order to avoid the decomposition of sodium ion halides during the preparation process, it is not advisable to select binders with good crystallinity and high polarity and strong polar organic solvents.

[0022] Preferably, the plasticizer includes at least one of succinonitrile (SN), dioxolane (DOL), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), fluoroethylene carbonate (FEC), and dimethyl ether (DME).

[0023] More preferably, the plasticizer is at least one of propylene carbonate and succinonitrile.

[0024] Preferably, the binder is at least one of polytetrafluoroethylene, polytetrafluoroethylene hexafluoroisopropylene block copolymer, ethylene propylene diene monomer rubber, and natural rubber.

[0025] When no organic solvent is introduced, polytetrafluoroethylene and polytetrafluoroethylene hexafluoroisopropylene block copolymer are preferably used as the binder; when an organic solvent is introduced, ethylene propylene diene monomer rubber and natural rubber are preferably used as the binder. The above binders can make the ion conductivity of the sodium ion halide solid electrolyte composite membrane material of the present invention greater than 0.35mS / cm under appropriate proportions.

[0026] Preferably, the sodium salt is at least one of sodium bis(trifluoromethanesulfonyl)imide and sodium difluorooxalatoborate.

[0027] Preferably, based on the mass percentage of the sodium ion halide, the content of the binder is 0.5-1%, the content of the sodium salt is 8-12%, and the mass of the plasticizer is 1.8-2.5% of the mass of the sodium salt.

[0028] By selecting the specific sodium ion halide, binder, sodium salt and plasticizer in the present invention, under the above-mentioned appropriate dosage ratio, the room temperature ionic conductivity of the sodium ion halide solid electrolyte composite membrane material can reach 0.51mS / cm, while maintaining good self-supporting performance of the composite membrane.

[0029] In a second aspect, the present invention provides a method for preparing the above-mentioned sodium ion halide solid electrolyte composite membrane material, which is selected from one of the following (a)-(c):

[0030] (a) mixing a sodium ion halide, a binder, a sodium salt, and a plasticizer, grinding the mixture, and applying pressure to obtain the sodium ion halide solid electrolyte composite membrane material;

[0031] (b) mixing a sodium ion halide, a binder, a sodium salt, and a plasticizer, grinding, heating, and pressurizing to obtain the sodium ion halide solid electrolyte composite membrane material;

[0032] (c) mixing sodium ion halide, a binder, a sodium salt, a plasticizer, and an organic solvent, grinding the mixture, coating the mixture on a surface of a base layer, and drying the mixture to obtain the sodium ion halide solid electrolyte composite membrane material.

[0033] Preferably, the grinding is at least one of hand grinding, ball grinding and roller pressing.

[0034] Further preferably, the grinding is ball milling, the ball-to-material ratio of the ball milling is (5-40):1, the ball milling time is 0.2-1h, and the ball milling speed is 100-1000rpm.

[0035] Preferably, in said (b), the heating temperature is 50-90°C.

[0036] Preferably, in (c), the amount of the organic solvent is 20-75% of the total mass of the raw materials (sodium ion halide, binder, sodium salt, plasticizer and organic solvent); further preferably, the amount of the organic solvent is 35-65% of the total mass of the raw materials.

[0037] Preferably, in said (c), the drying temperature is 55-115° C., and the drying time is 0.5-5 h.

[0038] In a third aspect, the present invention provides the use of the above-mentioned sodium ion halide solid electrolyte composite membrane material in the preparation of secondary batteries.

[0039] As a preferred embodiment of the present invention, the applications include: application of the above-mentioned sodium ion halide solid electrolyte composite membrane material in the preparation of electrolyte layers, electrode additives, and interface buffer layers of secondary batteries; and application of the above-mentioned sodium ion halide solid electrolyte composite membrane material mixed with a liquid electrolyte or an organic solvent to prepare a semi-solid or quasi-solid electrolyte for secondary batteries.

[0040] In a fourth aspect, the present invention also provides a secondary battery comprising a positive electrode layer, an electrolyte layer, a negative electrode layer, and a buffer layer, wherein at least one of the positive electrode layer, the electrolyte layer, the negative electrode layer, and the buffer layer contains the sodium ion halide solid electrolyte composite membrane material as described in any one of claims 1 to 7.

[0041] The above-mentioned secondary battery includes any one of a liquid sodium secondary battery, a solid-liquid mixed sodium secondary battery, a semi-solid sodium secondary battery, a quasi-solid sodium secondary battery, and an all-solid sodium secondary battery.

[0042] The secondary battery containing the sodium ion halide solid electrolyte composite membrane material provided by the present invention can be applied to consumer electronic products, electric bicycles, electric vehicles, robots, aerospace, solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies and energy storage equipment for communication base stations and other fields.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] The present invention provides a sodium ion halide solid electrolyte composite membrane material by selecting specific sodium ion halide, binder, sodium salt and plasticizer, which can maintain high room temperature ionic conductivity (>10 -4 S / cm), maintain good membrane self-supporting performance, and greatly simplify the assembly process of solid-state batteries. The sodium ion halide solid electrolyte composite membrane material provided by the present invention can be used in the preparation of secondary batteries and energy storage functional devices, and further used in consumer electronics, electric bicycles, electric vehicles, robots, aerospace, solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies and communication base stations. At the same time, the preparation method provided by the present invention is simple to operate, does not require special equipment and high temperature and high pressure environment, has good operational adaptability, and the raw materials are cheap and easy to obtain, which is conducive to actual production. DETAILED DESCRIPTION

[0045] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific examples. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0046] Example 1-1

[0047] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention. In the sodium ion halide solid electrolyte composite membrane material described in this embodiment, based on the mass percentage of sodium ion halide, the content of binder is 1.5%, the content of sodium salt is 8%, and the mass of plasticizer is 1.875% of the mass of sodium salt.

[0048] The preparation method of the sodium ion halide solid electrolyte composite membrane material described in this embodiment is:

[0049] (1) Raw material processing: the binder PTFE was placed in a vacuum oven at 100°C and dried for 48 hours; the sodium salt NaTFSI was placed in a vacuum oven at 120°C and dried for 48 hours, and then placed in a glove box filled with argon for equilibrium for more than 14 days; the plasticizer PC was placed in a glove box filled with argon for storage;

[0050] (2) Preparation: 2 g of sodium ion halide Na 1.8 NbO 0.9 Cl 5, 0.03g PTFE, 0.16g NaTFSI, and 0.003g PC are placed in an agate mortar and ground for 20 minutes to obtain a uniformly mixed powder; an appropriate amount of the powder is placed in a tablet press and maintained at a pressure of 300MPa for 1 minute to prepare the sodium ion halide solid electrolyte composite membrane material.

[0051] Example 1-2

[0052] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention, embodiment 1-2 is different from embodiment 1-1 only in that PTFE-HFP is selected as the binder instead of PTFE.

[0053] Examples 1-3

[0054] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention, embodiment 1-3 is different from embodiment 1-1 only in that PVDF is selected instead of PTFE as the binder.

[0055] Comparative Example 1-1

[0056] The only difference between Comparative Example 1-1 and Example 1-1 is that PMMA is selected as the binder instead of PTFE.

[0057] Comparative Example 1-2

[0058] The only difference between Comparative Example 1-2 and Example 1-1 is that PS is selected as the binder instead of PTFE.

[0059] Example 2-1

[0060] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention. In the sodium ion halide solid electrolyte composite membrane material described in this embodiment, based on the mass percentage of sodium ion halide, the content of binder is 0.5%, the content of sodium salt is 8%, and the mass of plasticizer is 1.875% of the mass of sodium salt.

[0061] The preparation method of the sodium ion halide solid electrolyte composite membrane material described in this embodiment is:

[0062] (1) Raw material processing: the binder PTFE was placed in a vacuum oven at 100°C and dried for 48 hours; the sodium salt NaTFSI was placed in a vacuum oven at 120°C and dried for 48 hours, and then placed in a glove box filled with argon for equilibrium for more than 14 days; the plasticizer PC was placed in a glove box filled with argon for storage;

[0063] (2) Preparation: 2 g of sodium ion halide NaTaOCl 5, 0.01 g PTFE, 0.16 g NaTFSI, and 0.003 g PC are placed in an agate mortar and ground for 20 minutes to obtain a uniformly mixed powder; an appropriate amount of the powder is placed in a tablet press and maintained at a pressure of 300 MPa for 1 minute to prepare the sodium ion halide solid electrolyte composite membrane material.

[0064] Example 2-2

[0065] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention, embodiment 2-2 is different from embodiment 2-1 only in that the amount of PTFE is changed to 0.02g; the content of the binder is 1% by mass percentage of the sodium ion halide.

[0066] Example 2-3

[0067] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention, embodiment 2-3 is different from embodiment 2-1 only in that the amount of PTFE is changed to 0.04g; the content of the binder is 2% by mass percentage of the sodium ion halide.

[0068] Comparative Example 2-1

[0069] The difference between Comparative Example 2-1 and Example 2-1 is that the amount of PTFE is changed to 0.005 g; the content of the binder is 0.25% based on the mass percentage of the sodium ion halide.

[0070] Comparative Example 2-2

[0071] The difference between Comparative Example 2-2 and Example 2-1 is that the amount of PTFE is changed to 0.1 g; the content of the binder is 5% based on the mass percentage of the sodium ion halide.

[0072] Example 3-1

[0073] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention. In the sodium ion halide solid electrolyte composite membrane material described in this embodiment, based on the mass percentage of sodium ion halide, the content of binder is 1%, the content of sodium salt is 8%, and the mass of plasticizer is 1.875% of the mass of sodium salt.

[0074] The preparation method of the sodium ion halide solid electrolyte composite membrane material described in this embodiment is:

[0075] (1) Raw material processing: the binder PTFE was placed in a vacuum oven at 100°C and dried for 48 hours; the sodium salt NaTFSI was placed in a vacuum oven at 120°C and dried for 48 hours, and then placed in a glove box filled with argon for equilibrium for more than 14 days; the plasticizer PC was placed in a glove box filled with argon for storage;

[0076] (2) Preparation: 2 g of sodium ion halide Na 1.6 HkDJ 0.8 Cl 4 , 0.02g PTFE, 0.16g NaFSI, and 0.003g PC are placed in an agate mortar and ground for 20 minutes to obtain a uniformly mixed powder; an appropriate amount of the powder is placed in a tablet press and maintained at a pressure of 300MPa for 1 minute to prepare the sodium ion halide solid electrolyte composite membrane material.

[0077] Example 3-2

[0078] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention, embodiment 3-2 is different from embodiment 3-1 only in that the component of the sodium salt is NaDFOB instead of NaFSI.

[0079] Comparative Example 3-1

[0080] The difference between Comparative Example 3-1 and Example 3-1 is that the component of the sodium salt is selected as NaBF 4 Replaces NaFSI.

[0081] Comparative Example 3-2

[0082] The difference between Comparative Example 3-2 and Example 3-1 is that NaCl is selected as the component of the sodium salt instead of NaFSI.

[0083] Example 4-1

[0084] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention. In the sodium ion halide solid electrolyte composite membrane material described in this embodiment, based on the mass percentage of the sodium ion halide, the content of the binder is 1%, the content of the sodium salt is 5%, and the mass of the plasticizer is 2% of the mass of the sodium salt.

[0085] The preparation method of the sodium ion halide solid electrolyte composite membrane material described in this embodiment is:

[0086] (1) Raw material processing: the binder PEO-co-PO was dried in a vacuum oven at 50°C for 48 h; the sodium salt NaTFSI was dried in a vacuum oven at 120°C for 48 h and then equilibrated in a glove box filled with argon for more than 14 days; the plasticizer SN was stored in a glove box filled with argon;

[0087] (2) Preparation: 2 g of sodium ion halide Na 1.6 S 0.8 Cl 3, 0.02 g PEO-co-PO, 0.1 g NaTFSI, and 0.002 g SN are placed in an agate mortar and ground for 20 minutes to obtain a uniformly mixed powder; an appropriate amount of the powder is placed in a tablet press and maintained at a pressure of 300 MPa and 65° C. for 5 minutes to prepare the sodium ion halide solid electrolyte composite membrane material.

[0088] Example 4-2

[0089] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention, embodiment 4-2 is different from embodiment 4-1 only in that the amount of NaTFSI is changed to 0.16g, the amount of SN is changed to 0.0032g, and the content of sodium salt is changed to 8% by mass percentage of sodium ion halide.

[0090] Example 4-3

[0091] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention, embodiment 4-3 is different from embodiment 4-1 only in that the amount of NaTFSI is changed to 0.24g, the amount of SN is changed to 0.0048g, and the content of sodium salt is changed to 12% by mass percentage of sodium ion halide.

[0092] Comparative Example 4-1

[0093] The difference between Comparative Example 4-1 and Example 4-1 is that the amount of NaTFSI and SN is reduced, and the content of sodium salt is changed to 1% by mass percentage of sodium ion halide.

[0094] Comparative Example 4-2

[0095] The difference between Comparative Example 4-2 and Example 4-1 is that the amount of NaTFSI and SN is increased, and the content of sodium salt is changed to 20% by mass percentage of sodium ion halide.

[0096] Example 5-1

[0097] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention. In the sodium ion halide solid electrolyte composite membrane material described in this embodiment, based on the mass percentage of sodium ion halide, the content of binder is 1%, the content of sodium salt is 10%, and the mass of plasticizer is 1% of the mass of sodium salt.

[0098] The preparation method of the sodium ion halide solid electrolyte composite membrane material described in this embodiment is:

[0099] (1) Raw material processing: the binder PEO-co-PO was dried in a vacuum oven at 50°C for 48 h; the sodium salt NaTFSI was dried in a vacuum oven at 120°C for 48 h and then equilibrated in a glove box filled with argon for more than 14 days; the plasticizer SN was stored in a glove box filled with argon;

[0100] (2) Preparation: 2 g of sodium ion halide Na 1.2 La 0.5 Ta 0.5 O 0.6 Cl 4 , 0.02 g PEO-co-PO, 0.2 g NaTFSI, and 0.002 g SN are placed in an agate mortar and ground for 20 minutes to obtain a uniformly mixed powder; an appropriate amount of the powder is placed in a tablet press and maintained at a pressure of 300 MPa and 65° C. for 5 minutes to prepare the sodium ion halide solid electrolyte composite membrane material.

[0101] Example 5-2

[0102] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention, embodiment 5-2 is different from embodiment 5-1 only in that the amount of SN is changed to 0.005g, so that the mass of the plasticizer is 2.5% of the mass of the sodium salt.

[0103] Comparative Example 5-1

[0104] The difference between Comparative Example 5-1 and Example 5-1 is that no plasticizer is used and SN is removed from the raw material.

[0105] Comparative Example 5-2

[0106] The difference between Comparative Example 5-2 and Example 5-1 is that the amount of SN is changed to 0.01 g, so that the mass of the plasticizer is 5% of the mass of the sodium salt.

[0107] Example 6-1

[0108] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention, in the sodium ion halide solid electrolyte composite membrane material described in this embodiment, based on the mass percentage of sodium ion halide, the content of binder is 1.5%, the content of sodium salt is 10%, and the mass of plasticizer is 2% of the mass of sodium salt.

[0109] The preparation method of the sodium ion halide solid electrolyte composite membrane material described in this embodiment is:

[0110] (1) Raw material processing: The binder NBR was placed in a vacuum oven at 100°C and dried for 48 hours; the sodium salt NaTFSI was placed in a vacuum oven at 120°C and dried for 48 hours, and then placed in a glove box filled with argon for equilibration for more than 14 days; the plasticizer SN was placed in a glove box filled with argon for storage; the molecular sieve treated at high temperature was placed in ethyl acetate and allowed to stand for more than 36 hours;

[0111] (2) Preparation: 2 g of sodium ion halide Na 2.2 YO 0.7 Cl 3.8 , 0.6 g 5% wt NBR solution, 0.2 g NaTFSI, 0.004 g SN, and 2.78 g ethyl acetate were placed in an agate mortar and ground for 3 minutes to obtain a uniformly mixed slurry; the slurry was evenly coated on an aluminum foil with a scraper and dried at 60° C. for 4 hours to prepare the sodium ion halide solid electrolyte composite membrane material.

[0112] Example 6-2

[0113] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention, embodiment 6-2 is different from embodiment 6-1 only in that methyl ethyl ketone is selected instead of ethyl acetate as the organic solvent.

[0114] Example 6-3

[0115] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention, embodiment 6-3 is different from embodiment 6-1 only in that EPDM is selected instead of NBR as the binder, and cyclohexane is selected instead of ethyl acetate as the organic solvent.

[0116] Example 6-4

[0117] An embodiment of the sodium ion halide solid electrolyte composite membrane material of the present invention, embodiment 6-4 is different from embodiment 6-1 only in that NR is selected instead of NBR as the binder and cyclohexane is selected instead of ethyl acetate as the organic solvent.

[0118] Comparative Example 6-1

[0119] The only difference between Comparative Example 6-1 and Example 6-1 is that PE is selected instead of NBR as the binder, and chloroform is selected instead of ethyl acetate as the organic solvent.

[0120] Comparative Example 6-2

[0121] The only difference between Comparative Example 6-2 and Example 6-1 is that PMMA is selected instead of NBR as the binder, and chloroform is selected instead of ethyl acetate as the organic solvent.

[0122] Effect Example 1

[0123] In order to explore the performance of the sodium ion halide solid electrolyte composite membrane material provided by the present invention, the composite membrane materials in the embodiments and comparative examples were tested as follows:

[0124] AC impedance test was carried out at a frequency of 8 MHz to 1 Hz. The impedance of the composite membrane was calculated based on the test results. The ionic conductivity of the composite membrane was obtained according to the formula σ=L / R·S. The results of ionic conductivity are compared in Tables 1-4 below.

[0125] From the comparison of the results in Table 1, we can see that:

[0126] Within the limited scope of the present invention, when other conditions remain unchanged and the type of binder is polytetrafluoroethylene (PTFE) and polytetrafluoroethylene hexafluoropropylene block copolymer (PTFE-HFP), the prepared sodium ion halide solid electrolyte composite membrane material has a higher ionic conductivity; when other binders outside the limit are selected, the ionic conductivity is significantly reduced; when the content of the binder is within the range of 0.5-2% of the present invention in terms of mass percentage of sodium ion halide, the material can maintain a higher room temperature ionic conductivity and give the composite membrane a certain self-supporting ability; an excessive amount of binder (Comparative Example 2-2) does not have ion transport ability and will significantly reduce the ionic conductivity of the sodium ion halide matrix, and when the binder is too little (Comparative Example 2-1), although the ionic conductivity of the composite membrane is high, it is observed that the self-supporting ability of the composite membrane is poor and it is fragile.

[0127] Table 1 Ionic conductivity of sodium ion halide solid electrolyte composite membranes with different binders and dosages

[0128]

[0129] From the comparison of the results in Table 2, we can see that:

[0130] Within the scope of the present invention, when other conditions remain unchanged, the type of sodium salt is sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) or sodium difluorooxalatoborate (NaDFOB), the prepared sodium ion halide solid electrolyte composite membrane material has a higher ionic conductivity; when other sodium salts outside the range are selected, the ionic conductivity may be significantly reduced; in terms of mass percentage of sodium ion halide, when the content of sodium salt is within the range of 5-12% of the present invention, the sodium salt can promote ion transport in the composite membrane and the room temperature ionic conductivity is high; when the sodium salt is excessive (Comparative Example 4-2), the self-crystallization agglomeration will cause the ion transport to be blocked; too little or too much sodium salt will cause the room temperature ionic conductivity of the composite membrane to be significantly reduced.

[0131] Table 2 Ionic conductivity of sodium ion halide solid electrolyte composite membrane under different sodium salts and dosages

[0132]

[0133]

[0134] From the comparison of the results in Table 3, we can see that:

[0135] Within the scope of the present invention, when other conditions remain unchanged and the content of the plasticizer is 1-3% of the mass of the sodium salt, an appropriate amount of plasticizer can inhibit the crystallization of the sodium salt, improve the sodium ion transmission capacity of the composite membrane, and the ion conductivity of the composite membrane is significantly higher; an excessive amount of plasticizer (Comparative Example 5-2) leads to poor ion transmission capacity and inhibits the transmission process of sodium ions; outside the scope of the present invention, too little or too much plasticizer will cause the ion conductivity of the composite membrane to be significantly reduced.

[0136] Table 3 Ionic conductivity of sodium ion halide solid electrolyte composite membranes at different plasticizer dosages

[0137]

[0138] From the comparison of the results in Table 4, we can see that:

[0139] When an organic solvent is introduced into the preparation method, other conditions remain unchanged within the scope defined by the present invention. When ethylene propylene diene monomer rubber (EPDM) and natural rubber (NR) are selected as binders, the room temperature ionic conductivity of the composite membrane is relatively high. In order to avoid decomposition of sodium ion halides during the preparation process, it is not advisable to select binders with good crystallinity and high polarity and strong polar organic solvents. When inappropriate binders and solvents outside the scope are introduced, the room temperature conductivity of the sodium ion halide solid electrolyte composite membrane material may be significantly reduced.

[0140] In summary, the present invention provides a sodium ion halide solid electrolyte composite membrane material, which can maintain high room temperature ionic conductivity and simplify the assembly process of solid-state batteries by optimizing the component selection and dosage of sodium ion halide, binder, sodium salt, and plasticizer.

[0141] Table 4 Ionic conductivity of sodium ion halide solid electrolyte composite membranes under different binders and solvents

[0142]

[0143] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A sodium ion halide solid electrolyte composite membrane material, characterized in that: The invention comprises the following components: sodium ion halide, a binder, a sodium salt and a plasticizer; The sodium ion halide is Na a MO b X c , a>0, b>0, c>0, M is at least one of Cr, V, Fe, Co, Ni, Ti, Sc, Lu, Y, Al, Ga, In, Yb, Tm, Er, Ho, Dy, Tb, Gd, Eu, Sm, Pm, Nd, Pr, Ce, La, Ti, Zr, Hf, Sn, Ge, Si, Nb, and Ta, and X is at least one of F, Cl, Br, and I; The binder comprises at least one of polytetrafluoroethylene, polytetrafluoroethylene hexafluoroisopropylene block copolymer, polyvinylidene fluoride, polyethylene oxide, polypropylene oxide, polyethylene oxide propylene oxide block copolymer, chloroprene rubber, nitrile rubber, ethylene propylene diene monomer rubber, and natural rubber; The sodium salt includes at least one of sodium bis(trifluoromethanesulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorophosphate, and sodium difluorooxalate borate; Calculated by mass percentage of the sodium ion halide, the content of the binder is 0.5-2%, the content of the sodium salt is 5-12%; the mass of the plasticizer is 1-3% of the mass of the sodium salt.

2. The sodium ion halide solid electrolyte composite membrane material according to claim 1, characterized in that: Organic solvents are also included.

3. The sodium ion halide solid electrolyte composite membrane material according to claim 2, characterized in that: The organic solvent includes at least one of N-methylpyrrolidone, dimethylformamide, dimethyl sulfoxide, chloroform, ethylene dichloride, benzene, toluene, ethyl acetate, butyl acetate, methyl ethyl ketone, cyclohexane, turpentine, and naphtha.

4. The sodium ion halide solid electrolyte composite membrane material according to claim 1, characterized in that: The plasticizer includes at least one of succinonitrile, dioxolane, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, ethylene carbonate, fluoroethylene carbonate, and dimethyl ether.

5. The sodium ion halide solid electrolyte composite membrane material according to claim 1, characterized in that: The binder is at least one of polytetrafluoroethylene, polytetrafluoroethylene hexafluoroisopropylene block copolymer, ethylene propylene diene monomer rubber, and natural rubber.

6. The sodium ion halide solid electrolyte composite membrane material according to claim 1, characterized in that: The sodium salt is at least one of sodium bis(trifluoromethanesulfonyl)imide and sodium difluorooxalatoborate.

7. The sodium ion halide solid electrolyte composite membrane material according to claim 1, characterized in that: Calculated by mass percentage of the sodium ion halide, the content of the binder is 0.5-1%, the content of the sodium salt is 8-12%; the mass of the plasticizer is 1.8-2.5% of the mass of the sodium salt.

8. The method for preparing the sodium ion halide solid electrolyte composite membrane material according to any one of claims 1 to 7, characterized in that: Select one of the following (a)-(c): (a) mixing a sodium ion halide, a binder, a sodium salt, and a plasticizer, grinding the mixture, and applying pressure to obtain the sodium ion halide solid electrolyte composite membrane material; (b) mixing a sodium ion halide, a binder, a sodium salt, and a plasticizer, grinding, heating, and pressurizing to obtain the sodium ion halide solid electrolyte composite membrane material; (c) mixing sodium ion halide, a binder, a sodium salt, a plasticizer, and an organic solvent, grinding the mixture, coating the mixture on a surface of a base layer, and drying the mixture to obtain the sodium ion halide solid electrolyte composite membrane material.

9. Use of the sodium ion halide solid electrolyte composite membrane material according to any one of claims 1 to 7 in the preparation of secondary batteries.

10. A secondary battery, characterized in that: It comprises a positive electrode layer, an electrolyte layer, a negative electrode layer and a buffer layer, wherein at least one of the positive electrode layer, the electrolyte layer, the negative electrode layer and the buffer layer contains the sodium ion halide solid electrolyte composite membrane material as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Solid electrolyte

    CN109690862A

  • Sodium ion composite solid electrolyte and preparation method thereof

    CN113506910A

  • Solid electrolyte material as well as preparation method and application thereof

    CN116344923A

  • Solid-state sodium ion battery and electric equipment

    CN219246873U

  • Solid polymer electrolyte based on modified cellulose and its use in lithium or sodium secondary batteries

    EP3422438A1